The Education of “Madrasa Students” Based on Self Confidence - Azam Syukur Rahmatullah (RIRAI Publisher, 2021)
This study examines the madrasa activity programs based on fostering student confidence. This research is important because the result can be used as role models for other schools or madrasa helping to develop the confidence of student in their schools or madrasa. This study uses a content analysis study approach. One of the Madrasa Aliyah that succeeded in developing a confidence based activity program is Madrasa Aliyah Plus Nururrohmah Tambaksari Kuwarasan, Kebumen. The madrasa has enriched various confidence-based activities since its inception in 2007 until now. This madrasa has excellent programs which fokus on helping students improve the quality of their confidence, which is not owned by other schools or madrasa. Some of the program activities referred to, are being crazy, selling in traditional markets, If I Become, a Real Work Madrasa, and examinations of scientific work which are tested by teachers with various degress. These various activities eventually bring students into personal that is not easily discouraged, not afraid to convey positive aspirations, dare to appear before the public, not ashamed to be an entrpreneur and able to handle personal problems and find solutions well.